The effect of cassava starch and modified cassava starch on the setting time of alginate impression: a laboratory experiment - Fransiska, Aria; Belia, Vinny Putri; Nofika, Reni; Yohana, Nelvi; Ramayanti, Sri (Universitas Padjadjaran, 2025)
Introduction: Alginate is the most commonly used impression material in dentistry for creating accurate impressions of soft and hard tissues in the oral cavity. Its properties can be modified by adding starch, as both alginate and starch contain polysaccharides. This modification affects not only alginate's dimensional stability but also its setting time. This study aimed to analyze cassava starch and modifies cassava starch on the setting time of alginate. Method: This experimental laboratory study measured the setting time of pure alginate, alginate with 40% cassava starch, and alginate with 40% modified cassava. Analyze data using Anova and Post Hoc LSD Test. Results: The fastest setting time was observed in pure alginate (89±2,23 seconds), followed by alginate with 40% modified cassava starch (150±3,01 seconds), and alginate with 40% cassava starch exhibited the longest setting time (211±3,57 seconds). A one-way ANOVA test showed significant differences between the setting times of pure alginate, alginate with 40% cassava starch, and alginate with 40% modified cassava starch. The post hoc LSD test showed that there were significant differences in each treatment group. Conclusion: The addition of cassava starch and modified cassava starch affects the setting time of alginate. Pure alginate sets the fastest, followed by alginate with modified cassava starch, while alginate with cassava starch has the longest setting time. The addition of both natural and modified starch has a significant effect on the setting time of alginate with different effects between the two.